2021
DOI: 10.1136/bmjopen-2020-043505
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient iodine nutrition status and the risk of pre-eclampsia: a systemic review and meta-analysis

Abstract: BackgroundAlthough subclinical hypothyroidism in pregnancy is one of the established risk factors for pre-eclampsia, the link between iodine deficiency, the main cause of hypothyroidism, and pre-eclampsia remains uncertain. We conducted a systematic review to determine the iodine nutrition status of pregnant women with and without pre-eclampsia and the risk of pre-eclampsia due to iodine deficiency.MethodsMEDLINE, EMBASE, Google Scholar, Scopus and Africa-Wide Information were searched up to 30th June 2020. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These findings correlate with previous case-control studies that reported a positive association between insufficient iodine intake and preeclampsia [ 12 , 30 , 31 ]. A recent systematic review found a significant difference in the mean UIC of preeclamptic and normotensive pregnant controls but no increased risk of preeclampsia among pregnant women with UIC < 150 μg/L in the included cohort studies [ 32 ]. The study was, however, limited by the very few numbers of included studies and high heterogeneity across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings correlate with previous case-control studies that reported a positive association between insufficient iodine intake and preeclampsia [ 12 , 30 , 31 ]. A recent systematic review found a significant difference in the mean UIC of preeclamptic and normotensive pregnant controls but no increased risk of preeclampsia among pregnant women with UIC < 150 μg/L in the included cohort studies [ 32 ]. The study was, however, limited by the very few numbers of included studies and high heterogeneity across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the findings between these studies and ours could partly be accounted for by the timing of the iodine and thyroid function tests. While the iodine and thyroid function status in our study were measured in the third trimester, the cohort studies in the systematic review [ 32 ], as well as the study by Richie et al [ 33 ], estimated the risk of preeclampsia based only on the iodine and thyroid function status estimates in the first trimester. This approach did not consider the impact of the iodine nutritional state in the second half of pregnancy on the risk of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis in euthyroid women showed that the pooled prevalence of preterm birth, low birth weight and hypertensive disorders were not associated with first trimester urinary iodine levels ( 31 ). Another systematic review and meta-analysis suggested that even though pre-eclamptic women presented lower urinary iodine levels, additional studies are needed to conclude on the association with iodine deficiency ( 32 ). Interestingly, in a Norwegian cohort study, iodine supplement use initiated before pregnancy reduced the risk of preeclampsia but not that of other measured adverse outcomes; this study did not address miscarriages ( 33 ).…”
Section: Discussionmentioning
confidence: 99%